2017
DOI: 10.17546/msd.341826
|View full text |Cite
|
Sign up to set email alerts
|

A novel volumetric analysis using cad/cam scanners in gingival recession treatment

Abstract: Objective: In this study, randomized clinical trial (RCT), the aim was to compare clinical periodontal data of subepithelial connective tissue graft (SCTG) group and SCGT+enamel matrix derivatives (EMD) group in terms of gained gingiva volume (GGV) and gained gingiva surface area (GGSA) by scanners of computeraided design/computer-aided manufacturing (CAD/CAM) devices. Material and Methods:In this study, a total of 35 Miller class I-II gingival recession defects were involved (n=17 in SCTG group, n=18 in SCTG+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This system can be used to take direct images from the oral cavity or from models created after impressions are taken from the patients [21]. Recently, this technique was successfully used for volumetric analyses after gingival recession treatment [22]. In another study, Wiranto et al [19] reported that intraoral scanning is a valid and reliable method with high reproducibility for diagnostic measurements in the field of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…This system can be used to take direct images from the oral cavity or from models created after impressions are taken from the patients [21]. Recently, this technique was successfully used for volumetric analyses after gingival recession treatment [22]. In another study, Wiranto et al [19] reported that intraoral scanning is a valid and reliable method with high reproducibility for diagnostic measurements in the field of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, intraoral scanning was more and more used to assess the length and volume of gingival recessions * email: eugenia_totu@yahoo.com All the authors have equally contributed to the manuscript, and they should be regarded as main authors. [2][3][4][5], or to document soft tissue shape and irregularity [1].…”
mentioning
confidence: 99%
“…In the last years, intraoral scanning was more and more used to assess the length and volume of gingival recessions * email: eugenia_totu@yahoo.com All the authors have equally contributed to the manuscript, and they should be regarded as main authors. [2][3][4][5], or to document soft tissue shape and irregularity [1].…”
mentioning
confidence: 99%